Commit, hide and escape: the story of Plasmodium gametocytes. Issue 13 (16th July 2018) - Beri, Divya; Balan, Balu; Tatu, Utpal
Abstract: Malaria is the major cause of mortality and morbidity in tropical countries. The causative agent, Plasmodium sp., has a complex life cycle and is armed with various mechanisms which ensure its continuous transmission. Gametocytes represent the sexual stage of the parasite and are indispensable for the transmission of the parasite from the human host to the mosquito. Despite its vital role in the parasite's success, it is the least understood stage in the parasite's life cycle. The presence of gametocytes in asymptomatic populations and induction of gametocytogenesis by most antimalarial drugs warrants further investigation into its biology. With a renewed focus on malaria elimination and advent of modern technology available to biologists today, the field of gametocyte biology has developed swiftly, providing crucial insights into the molecular mechanisms driving sexual commitment. This review will summarise key current findings in the field of gametocyte biology and address the associated challenges faced in malaria detection, control and elimination.